2021
DOI: 10.1001/jamapsychiatry.2021.0976
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Opioid Agonist Treatment With All-Cause Mortality and Specific Causes of Death Among People With Opioid Dependence

Abstract: IMPORTANCE Mortality among people with opioid dependence is higher than that of the general population. Opioid agonist treatment (OAT) is an effective treatment for opioid dependence; however, there has not yet been a systematic review on the relationship between OAT and specific causes of mortality.OBJECTIVE To estimate the association of time receiving OAT with mortality.DATA SOURCES The Embase, MEDLINE, and PsycINFO databases were searched through February 18, 2020, including clinical trial registries and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
233
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(244 citation statements)
references
References 87 publications
7
233
4
Order By: Relevance
“…It is plausible that many clients who died of a drug poisoning death while registered on the OAT register had in fact left treatment because global evidence clearly demonstrates the protective effects of treatment versus leaving treatment. 37 Future work is necessary to ascertain whether the drugs involved in drug poisoning deaths vary depending on where a client is in terms of their OAT journey at the time of death.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…It is plausible that many clients who died of a drug poisoning death while registered on the OAT register had in fact left treatment because global evidence clearly demonstrates the protective effects of treatment versus leaving treatment. 37 Future work is necessary to ascertain whether the drugs involved in drug poisoning deaths vary depending on where a client is in terms of their OAT journey at the time of death.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Although COVID-19 presents a significant threat to everyone, people with opioid dependence are particularly vulnerable to the disease and its sequelae, as they have a higher burden of co-existing health problems 1 , with many living in areas of social deprivation, with poor-quality housing or homelessness 2 . Opioid agonist treatment (OAT), using methadone or buprenorphine, is the first line treatment for opioid dependence, as it has been shown to be safe and effective in suppressing illicit opioid use 3,4 , improving mental and physical well-being 5 , and reducing mortality 6 . In fact, a recent systematic review identified that risk of all-cause mortality, overdose, suicide, alcohol-related, cancer and cardiovascular-related mortality, were significantly lower for people with opioid dependence on OAT compared to those not on OAT 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Opioid agonist treatment (OAT), using methadone or buprenorphine, is the first line treatment for opioid dependence, as it has been shown to be safe and effective in suppressing illicit opioid use 3,4 , improving mental and physical well-being 5 , and reducing mortality 6 . In fact, a recent systematic review identified that risk of all-cause mortality, overdose, suicide, alcohol-related, cancer and cardiovascular-related mortality, were significantly lower for people with opioid dependence on OAT compared to those not on OAT 6 . The authors highlighted the importance of increasing access to OAT and maintaining people on OAT who are in critical need of treatment to reduce their mortality risk 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations